Multimodal Counseling Strategy for Claustrophobia in Clinical Practice: A Case Report - Nabilaa Faizatuz Zuhriyah (Asesment : Journal Of Counseling Guidance, 2025)
Background: The COVID-19 pandemic has significantly increased anxiety-related disorders, particularly claustrophobia. Factors like prolonged lockdowns and mask-wearing have triggered or exacerbated claustrophobic symptoms, even in individuals without prior tendencies. The importance of developing evidence-based counseling strategies to address such post-pandemic mental health issues is crucial.Objective: This study aims to document and assess the effectiveness of a multimodal counseling strategy for treating claustrophobia that emerged or intensified during the pandemic. The goal is to provide a practical framework for addressing this specific phobia in clinical practice.Method: A case study methodology was employed, focusing on a 32-year-old female who exhibited severe claustrophobic symptoms post-pandemic. A 12-session intervention integrated cognitive-behavioral techniques, psychoeducation, graduated exposure, and mindfulness-based strategies. Data collection included standardized measures and self-reports across multiple assessment points.Findings and Implications: The treatment resulted in a 72% reduction in claustrophobia severity and significant improvements in general anxiety and stress levels. The integration of multiple therapeutic approaches proved effective in reducing symptoms and improving functional capacity. These findings suggest that multimodal interventions can be a robust solution for pandemic-induced claustrophobia and other anxiety disorders.Conclusion: The study highlights the effectiveness of multimodal counseling for claustrophobia, demonstrating significant symptom reduction and functional recovery. The results offer a clinically replicable framework for treating claustrophobia in post-pandemic contexts and suggest directions for future research and practice.